Identification of Two Eukaryote-Like Serine/Threonine Kinases Encoded by Chlamydia trachomatis Serovar L2 and Characterization of Interacting Partners of Pkn1 - Verma, Anita (American Society for Microbiology, 2003)
Genome sequencing of C. trachomatis serovar D revealed the presence of three putative open reading frames (ORFs), CT145 (Pkn1), CT673 (Pkn5), and CT301 (PknD), encoding eukaryote-like serine/threonine kinases (Ser/Thr kinases). Two of these putative kinase genes, CT145 and CT301, were PCR amplified from serovar L2, cloned, and sequenced. Predicted translation products of the ORFs showed the presence of conserved kinase motifs at the N terminus of the proteins. CT145 and CT301 (encoding Pkn1 and PknD, respectively) were expressed in Escherichia coli as GST fusion proteins. In vitro kinase assays with Escherichia coli-derived glutathione S-transferase fusion proteins showed autophosphorylation of Pkn1 and PknD, indicating that they are functional kinases. Gene expression analysis of these kinase genes in Chlamydia by reverse transcriptase PCR indicated expression of these kinases at the early mid phase of the developmental cycle. Immunoprecipitated native chlamydial Pkn1 and PknD proteins also showed autophosphorylation in an in vitro kinase assay. Phosphoamino acid analysis by thin-layer chromatography confirmed that Pkn1 and PknD are phosphorylated on both serine and threonine residues. Interaction of Pkn1 and PknD with each other as well as interaction of Pkn1 with inclusion membrane protein G (IncG) was demonstrated by using a bacterial two-hybrid system. These interactions were further suggested by phosphorylation of the proteins in in vitro kinase assays. This report is the first description of the existence of functional Ser/Thr kinases in Chlamydia. The results of these findings should lead to a better understanding of how Chlamydia interact and interfere with host signaling pathways, since kinases represent potential mediators of the intimate host-pathogen interactions that are essential to the intracellular life cycle of Chlamydia.